Pengaruh Fear of Missing Out terhadap Perilaku Phubbing pada Ibu Rumah Tangga Kota Padang - Az-zahra, Atikah; Dwatra, Free Dirga (MASALIQ, 2024)
The existence of phubbing behavior in housewives is seen from housewives who often use smartphones even though they are interacting face to face. The purpose of this study was to determine the influence of fear of missing out on phubbing behavior in housewives. This study is a type of quantitative correlational research. The sample in this study were housewives representing each sub-district of Padang City totaling 110 people with 10 housewives in each sub-district. The data collection technique used by the researcher was a questionnaire. The data analysis technique in this study used the normality test and simple linear regression test. The results showed that Fear of Missing Out (FoMO) in housewives in Padang City was generally in the moderate category. Phubbing behavior in housewives in Padang City was generally in the moderate category. There is an influence between Fear of Missing Out (FoMO) on Phubbing behavior in housewives in Padang City.